A Nantucket wedding [large type] : a novel - Thayer, Nancy, 1943- (Center Point Large Print, 2018)
"While placing the finishing touches on her summer nuptials, Alison is anxious to introduce her fiancé, David, to her grown daughters, hoping to give the siblings a chance to reconnect and to get to know David's grown children. Revelations, intrigue, and resentments will make this a wedding to remember"--